ASTEROID: A new clinical stereotest on an autostereo 3D tablet - Vancleef, K; Serrano-Pedraza, I; Sharp, C; Slack, G; Black, C; Casanova, T; Hugill, J; Rafiq, S; Burridge, J; Puyat, V; Enongue, J; Gale, H; et al. (Association for Research in Vision and Ophthalmology, 2019)
Purpose: To describe a new stereotest in the form of a game on an autostereoscopic tablet computer designed to be suitable for use in the eye clinic and present data on its reliability and the distribution of stereo thresholds in adults. Methods: Test stimuli were four dynamic random-dot stereograms, one of which contained a disparate target. Feedback was given after each trial presentation. A Bayesian adaptive staircase adjusted target disparity. Threshold was estimated from the mean of the posterior distribution after 20 responses. Viewing distance was monitored via a forehead sticker viewed by the tablet's front camera, and screen parallax was adjusted dynamically so as to achieve the desired retinal disparity. Results: The tablet must be viewed at a distance of greater than ∼35 cm to produce a good depth percept. Log thresholds were roughly normally distributed with a mean of 1.75 log10 arcsec = 56 arcsec and SD of 0.34 log10 arcsec = a factor of 2.2. The standard deviation agrees with previous studies, but ASTEROID thresholds are approximately 1.5 times higher than a similar stereotest on stereoscopic 3D TV or on Randot Preschool stereotests. Pearson correlation between successive tests in same observer was 0.80. Bland-Altman 95% limits of reliability were ±0.64 log10 arcsec = a factor of 4.3, corresponding to an SD of 0.32 log10 arcsec on individual threshold estimates. This is similar to other stereotests and close to the statistical limit for 20 responses. Conclusions: ASTEROID is reliable, easy, and portable and thus well-suited for clinical stereoacuity measurements. Translational Relevance: New 3D digital technology means that research-quality psychophysical measurement of stereoacuity is now feasible in the clinic.